Individualized breakfast programs or glycogen super-compensation: which is the better performing strategy? Insights from an Italian Soccer Referees` cohort - Regnoli, R.; Rovelli, M.; Gianturco, V.; Pregliasco, F. E.; Bodini, B. D.; Gianturco, L. (Frontiers in Sports and Active Living, 2020)
The role of soccer referees has growth in importance along the last decades and so, the attention about their performance which may be influenced and improved with specific and evolved training programs. Nowadays, multiple specialists work as a team in order to obtain that. Moreover, for athletes it is more and more important taking care of nutrition. By considering such items, in this study we wanted to investigate nutritional habits of a group of referees belonging to Italian Soccer Referees` Association (on behalf of AIA-FIGC). Our main aim was to spread a "culture of nutrition" in refereeing starting with a survey on their breakfast attitudes. And in order to disseminate such "culture", we have not chosen top-level elite referees but younger subjects (despite an average 4-years` experience). So, we wanted to enroll 31 young referees (aged 22.74±1.79, BMI 22.30±1.53) and asked them about their breakfast habits. Then, for measuring their performance we used the conventional fitness test named Yo-Yo (YYiR1) performed in three different sessions (test 1, test 2, test 3). Respectively: test 1 made without any nutritional indications; test 2 after an individualized breakfast suggestions given by a designed dietician; test 3 after an individualized glycogen super-compensation strategy. Wilcoxon statistical analysis told us that referees following an individualized breakfast strategy may enhance their performance (p<0.0001) whereas any significant effects was observed with glycogen super-compensation option. However, further studies will be necessary to better address the topic and clarify if high-carbohydrates (high-CHO) intake may be useful like in other endurance sports.